REALISTIC MATHEMATIC EDUCATION (RME) DALAM MENINGKATKAN HASIL BELAJAR SISWA MI DI MALANG - Asfa Riha Farah Adiba (Universitas Islam Malang, 2020)
This study is to find out the learning problems in MI Cemorokandang kedungkandang malang, namely about the problem of low student learning outcomes and students' knowledge of mathematics subjects in class III on multiplication and division material. This study uses a realistic mathematic education learning model. Studying mathematics is including increasing students' knowledge in thinking logically, rationally, critically, carefully, effectively, and efficiently. Therefore, as a teacher must be able to apply effective and efficient learning so students can understand to work on and solve mathematical learning problems. However, the teacher cannot apply it because the teacher does not understand the problems that arise from the model, the media or the characteristics of their students. In this case the researcher will discuss realistic mathematics learning in class III at MI Cemorokandang Kedungkandang Malang, the problems experienced by teachers in mathematics learning are low levels and the problems faced by students in learning mathematics at MI Cemorokandang Kedungkandang Malang